Bone Marrow Lymphocyte Populations of Innate Immunity in Breast Cancer Patients (Global Journal of Medical Research, 2020)
The innate immunity system plays an important role in antitumor protection, and more and more attention has been paid to its study recent years. However, the interrelation of the effect or subpopulations of the cells of the innate immunity in bone marrow with clinical parameters is poorly studied. The paper presents data on the composition of innate immune cells in the bone marrow of 64 patients with operable breast cancer, as well as 10 women with benign processes in the mammary gland. As result a significant correlation between the molecular subtype of cancer and the level of B1-lymphocytes was identified. Breast cancer patients levels of NK cells (CD56 + CD3-and CD16 + CD3-) in the bone marrow were significantly higher in patients with low proliferative activity (Ki-67 less than 20%), compared to patients having a high tumor proliferation index. Populations of NK cells were interrelated with erythropoiesis in patients with breast cancer and were significantly higher in cases of reduced basophilic and polychromatophilicnormoblasts.
Keywords: innate immunity breast cancer; tcr#x3B3; #x3B4; cells; b1-lymphocytes; nk cells; hematopoiesis